Piecing it all together [large type] - Gould, Leslie, 1962- (Plain patterns, 2021)
"After Savannah Mast's fiancé dumps her a week before their wedding, she flees California for the safety of her Amish grandmother's farm near Nappanee, Indiana, where she used to spend her summers. Savannah intends her stay to be brief, but when an Amish woman goes into labor in the middle of a blizzard and needs Savannah's help, she finds herself unexpectedly entangled in their family's drama. The woman's oldest daughter, Miriam, goes missing and Savannah's childhood friend Tommy Miller is implicated. Jane Berger, the local historian and owner of a nearby quilt shop, tells a similar tale of another woman's disappearance in the 1800s, inspiring Savannah to do all she can to help with the search for Miriam. But when Tommy's own cousin testifies against him, she isn't sure who she can trust. And when events stir up painful memories of her mother, she must face her own truth: that her engagement isn't the only thing in her life that is broken."--